Aggrecan and COMP Improve Periosteal Chondrogenesis by Delaying Chondrocyte Hypertrophic Maturation - Caron, Marjolein M. J.; Janssen, Maarten P. F.; Peeters, Laura; Haudenschild, Dominik R.; Cremers, Andy; Surtel, Don A. M.; van Rhijn, Lodewijk W.; Emans, Pieter J.; Welting, Tim J. M. (Frontiers in Bioengineering and Biotechnology, 2020)
The generation of cartilage from progenitor cells for the purpose of cartilage repair is often hampered by hypertrophic differentiation of the engineered cartilaginous tissue caused by endochondral ossification. Since a healthy cartilage matrix contains high amounts of Aggrecan and COMP, we hypothesized that their supplementation in the biogel used in the generation of subperiosteal cartilage mimics the composition of the cartilage extracellular matrix environment, with beneficial properties for the engineered cartilage. Supplementation of COMP or Aggrecan was studied in vitro during chondrogenic differentiation of rabbit periosteum cells and periosteum-derived chondrocytes. Low melting agarose was supplemented with bovine Aggrecan, COMP or vehicle and was injected between the bone and periosteum at the upper medial side of the tibia of New Zealand white rabbits. Generated subperiosteal cartilage tissue was analyzed for weight, GAG and DNA content. Key markers of different phases of endochondral ossification were measured by RT-qPCR. For the in vitro experiments, no significant differences in chondrogenic marker expression were detected following COMP or Aggrecan supplementation, while in vivo favorable chondrogenic marker expression was detected. Gene expression levels of hypertrophic markers were significantly decreased in the Aggrecan and COMP supplemented conditions compared to controls. The wet weight and GAG content of the in vivo generated subperiosteal cartilage tissue was not significantly different between groups. Data demonstrate the potential of Aggrecan and COMP to favorably influence the subperiosteal microenvironment for the in vivo generation of cartilage for the optimization of cartilage regenerative approaches.